Morbidity profile of communicable diseases in a tertiary care hospital of Chandrapur, Maharashtra - Dhoble, Shital S.; Atram, Devishri P.; Kubde, Sanjay S.; Naitam, Anil (International Journal Of Community Medicine And Public Health, 2018)
Background: Worldwide, developed and developing countries are facing the double burden of communicable and non-communicable diseases. However, developing countries like India is more exposed and vulnerable due to multitude of factors. Objectives were to study the morbidity patterns of communicable diseases of indoor patients at tertiary care hospital and find out the seasonal distribution of the communicable diseases. Methods: A retrospective study was done over a period of 1 year from April 2016 to March 2017. 4766 admitted patients of communicable diseases were included using universal sampling method. Diagnosis was categorized as per International classification of Disease (ICD) 10 classification. Data was analyzed using spss 16. Results: Out of the total 4766 admitted patients, 62% were females and 38% were males. 56.40% patients admitted in the most productive age group (15-45 years) followed by 14.35% and 8.06% geriatric population and under 5 children respectively. Peak in admission was seen in monsoon season (July to Sept.). 34.54% patients were admitted for bacterial cause followed by 30.03% acute gastroenteritis (AGE). AGE, viral fever, malaria were more commonly seen in female while typhoid, measles, tuberculosis were more commonly seen in male. Conclusions: Many diseases have a seasonal variation and the burden of these diseases could be reduced if we take measures to detect the changes in their trend through the implementation of surveillance programs.